New Ventures, Internationalization, and Asymmetric Grin Curve: Analysis of Taiwan’s Big Data - Lin, Jwu-Rong; Huang, Chen-Jui; Chen, Ching-Yu; Shiau, Huey-Ling; Yeh, Yan-Chen (Advances in Technology Innovation, 2019)
Under globalization, small and medium enterprises (SMEs) that predominate Taiwan’s economy have been primarily original equipment manufacturers (OEMs) continuing to adjust operating strategies in order to extend supply chains and enhance competitiveness. This paper adopts the big data composed of 104,377 Taiwanese manufacturers from the 2011 Industry, Commerce, and Service Census to assess impact of the business life cycle, brand revenue, R&D spending, and internationalization on value creation. Major findings are as follows. First, the link of the firm’s operating years with value creation is characterized by a quadratic U-shaped curve where the minimum point corresponds to 15 years of operation, suggesting a cost of lower value added for new ventures at the early stage of development. Second, a reversed U-shaped curve of value creation is found as regards brand revenue and R&D spending, with the greater impact of the latter. Third, the impact of overseas investment and export expansion is also captured by a reversed U-shaped curve, with greater impact for the former. Fourth, an asymmetric grin curve rather than a smile curve is found in Taiwan’s manufacturers, whose value creation can be strengthened by strategies that focus on the learning curve, internationalization, internet, operating scale, and capital intensity.